Effects of seasonal variation on the characteristics of stranded marine debris within Rambut Island Wildlife Reserve, Indonesia - Rahman, Lucky; Zamani, Neviaty Putri; Ismet, Meutia Samira; Cordova, Muhammad Reza (Jurnal Kelautan Tropis, 2024)
Monitoring and assessing the items stranded on shorelines is a crucial step in addressing the threat posed by marine debris to our ocean. The objective of this study is to examine the occurrence and categorize marine debris that accumulates on the beach and mangrove area of Pulau Rambut Wildlife Reserve from the transitional season 2 to the rainy season. The abundance of marine debris is significant in transitional season 2. There is no significant difference between different seasons. The dominant form of debris among all macrodebris categories during transitional season 2 was plastic, accounting for 46.38% of the total. Single-use plastics like styrofoam, shoes, sandals, gloves, plastic wrap, and plastic sachets were found to be the most common types of large-scale plastic debris, comprising 60% of total macroplastic debris. The debris found on Rambut Island is believed to originate from debris carried by rivers that flow into Jakarta Bay. The presence of seasonal winds, currents, waves, and tides further contribute to the accumulation of debris in this area.